Pertumbuhan Bakteri Hasil Isolasi dari Tanah Perkebunan yang Tumbuh pada Media Mengandung Pestisida Propoksur dan Karbaril - Imamuddin, Hartati; Laili, Nur; Rahmansyah, Maman (JURNAL BIOLOGI INDONESIA, 2012)
Growth Capacity of Soil Bacteria Isolates Obtained from Estate Area from Media Containing Propoxur and Carbaryl. Isolation actions have been carried out with three soil samples derived from soil estate of pine apple, sugar cane, and banana in Lampung area, Southern Sumatra. The isolates were grown in the selected media containing carbaryl insecticide, and herbicide of diuron and bromocyl. The highest and vigorous growth isolates have gathered from threedifferent soil samples, and subsequently named GGPC, GM, and NTF isolates. Furthermore, those isolates were studied through the growth rate in the media containing propoxur and carbaryl in the nutrient rich liquid (NB) and compared to limited mineral (MM). All of the isolates grew faster against pesticides in the liquid medium of NB compared to MM. High correlated value among parameters nurtured as due to bacterial population and those processes were not affected by media composition. The GM isolate showed similar pattern during propoxur decrease along with incubation even though the rate of pesticide elimination from the media was higher in the rich nutrient liquid media (NB) compared to MM.Keywords: microbe isolate, pesticide, propoxur, carbaryl